The Global Dimension of Poverty in the Muslim World: A Numerical Assessment - Al-Roubale, Amer (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Global Dimension of Poverty in the Muslim World: A Numerical Assessment